Effect of protein sources on growth, survival, feed conversion and protein utilization in fry of red tilapia (Oreochromis niloticus) - Neethiselvan, N; Manikandavelu, D; Jasmine, G Indra; Venkataramani, V K (Indian Journal of Fisheries, 2011)
Feeding experiment conducted to determine the protein requirement of red tilapia (Oreochromis niloticus) revealed a significantly (P<0.01) higher weight gain when fed with 35% protein diet than those with 25 and 30% protein, irrespective of the protein sources used. Weight gain of fish fed with 40% dietary protein did not differ significantly (P>0.01) from those fed with 35% protein. However, the feed conversion efficiency and protein efficiency ratio of the animals fed with 35 and 40% protein diet varied significantly (P<0.01) revealing the optimum protein requirement of red tilapia in the range of 35-40%. While fish fed with fishmeal based diets recorded good survival rate at all protein levels, ensilage based feeds recorded poor survival rate at lower protein levels viz. 25 and 30%. On the basis of specific growth rate, feed conversion efficiency and protein conversion ratio, fish ensilage based diets were on par with that of fishmeal based diets, suggesting fish ensilage as an alternative source of protein in the feeds of red tilapia